Avaliação da política de incentivos fiscais do setor calçadista no Estado do Ceará - Jereissati, Henrique José Leal (2024)
This study analyzes the importance of the footwear sector in Ceará and the relevance of the tax incentives offered by the Industrial Development Fund (FDI) for regional economic development. The main objective was to evaluate the economic impact of FDI incentives on the footwear sector in Ceará between 2010 and 2021, focusing on job creation, GDP growth, and the increase in economic activity in the benefited municipalities. The adopted methodology was quantitative, using concrete economic data related to production, employment, and other relevant indicators. The balanced dynamic panel estimation technique was employed, allowing the analysis of how the Value Added Fiscal (VAF), GDP, and sector employment in the municipalities of Ceará are influenced by FDI fiscal incentives. The results confirm the effectiveness of FDI tax incentives in promoting regional economic development, highlighting a positive association between per capita FDI disbursements and the increase in per capita GDP. Notably, FDI tax incentives showed a strong correlation with the increase in per capita Value Added Fiscal (VAF), evidencing a direct impact on the economic contribution of the benefited municipalities. Additionally, a significant growth in job creation in the footwear sector was observed, demonstrating that per capita FDI disbursements are a crucial factor for employment expansion in this specific sector. In conclusion, this study reinforces the importance of FDI tax incentives as an effective tool to promote economic development in the footwear sector in Ceará, providing important insights for the formulation of public policies aimed at sustainable and balanced state development. Future research can focus on evaluating the impact of FDI in other sectors of Ceará's economy, providing a broader view of the benefits and challenges of tax incentives in different economic contexts.